2019
DOI: 10.1017/pasa.2019.24
|View full text |Cite
|
Sign up to set email alerts
|

SN1991bg-like supernovae are associated with old stellar populations

Abstract: SN1991bg-like supernovae are a distinct subclass of thermonuclear supernovae (SNe Ia). Their spectral and photometric peculiarities indicate their progenitors and explosion mechanism differ from 'normal' SNe Ia. One method of determining information about supernova progenitors we cannot directly observe is to observe the stellar population adjacent to the apparent supernova explosion site to infer the distribution of stellar population ages and metallicities. We obtain integral field observations and analyse t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…In fact, both SNe 2018cqj and 2016jae appeared in the outskirts of their putative host galaxies, suggesting either that they are halo objects, whereas the host of SN 2018fhw was a dwarf elliptical. This is consistent with the progenitor environment of the majority of the 91bg-like and transitional SNe (see, e.g., Panther et al 2019), rather than with that of Type Ia-CSM SNe, which are found in star-forming galaxies (see, e.g., Hamuy et al 2003;Prieto et al 2007;Dilday et al 2012;Silverman et al 2013).…”
Section: Discussion and Summary On The Nature Of Sn 2016jae And Its P...supporting
confidence: 81%
“…In fact, both SNe 2018cqj and 2016jae appeared in the outskirts of their putative host galaxies, suggesting either that they are halo objects, whereas the host of SN 2018fhw was a dwarf elliptical. This is consistent with the progenitor environment of the majority of the 91bg-like and transitional SNe (see, e.g., Panther et al 2019), rather than with that of Type Ia-CSM SNe, which are found in star-forming galaxies (see, e.g., Hamuy et al 2003;Prieto et al 2007;Dilday et al 2012;Silverman et al 2013).…”
Section: Discussion and Summary On The Nature Of Sn 2016jae And Its P...supporting
confidence: 81%
“…Some simulations involving higher mass CO WD cores have been carried out (e.g. Pakmor et al 2021), which yield interesting synthetic observables that may be of interest in the era of large-scale surveys by the likes of the Vera C. Rubin Observatory.…”
Section: Discussionmentioning
confidence: 99%
“…converting the helium to carbon, thereby removing helium), there are certain regions of parameter space during stable Roche lobe overflow where helium will be accumulated on the CO WD and will not burn (Piersanti, Tornambé & Yungelson 2014). Is is also plausible that a somewhat low-mass CO white dwarf with a rather thick helium surface layer could be realized through a merging event (Crocker et al 2017), though detailed studies of such a situation remain largely unexplored, particularly in 3D (but see Pakmor et al 2021).…”
Section: P Ro S P E C T S F O R D E T E C Ta B I L I T Ymentioning
confidence: 99%
“…This results in an underestimate of supernova rates from systems with long-delay times (e.g. Panther et al 2019), as it does not take into account the total mass that formed into stars -most massive stars that formed in the past will have since exploded as supernovae. As the binary population synthesis calculation depends on knowing the total mass that formed into stars, our calculation underestimates the rate.…”
Section: Discussionmentioning
confidence: 99%